2017
DOI: 10.1002/ijc.30856
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and demographic disparities in breast cancer stage at presentation and survival: A Swiss population‐based study

Abstract: Novelty and Impact (max. 75 words):Switzerland has universal health insurance coverage, high health expenditures, and one of the highest life expectancies in the world. Despite that, this study describes high-risk groups for later-stage breast cancer (BC) diagnosis and higher BC specific mortality in Switzerland. Women of lower socioeconomic position were more likely to present with later-stage BC and showed poorer disease-specific survival. Notably, survival inequalities could not be explained by socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 44 publications
5
31
1
10
Order By: Relevance
“…Interestingly, while education level could modify the effect of psychological distress on accepting screening for colorectal and lung cancers, it did not exhibit this effect on breast cancer screening in countries with low cancer screening rates . From the perspective of survival, our study supported education as a protective factor for BCSS and OS (Table ), which was consistent with results of previous studies in which women with high education levels had better survival than women with low education levels, which suggests that education helps women understand the benefits of conducting breast self‐examination and accepting routine breast cancer screening programs, and it can improve patient access to effective treatments . However, the findings are not entirely in accordance with this point.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, while education level could modify the effect of psychological distress on accepting screening for colorectal and lung cancers, it did not exhibit this effect on breast cancer screening in countries with low cancer screening rates . From the perspective of survival, our study supported education as a protective factor for BCSS and OS (Table ), which was consistent with results of previous studies in which women with high education levels had better survival than women with low education levels, which suggests that education helps women understand the benefits of conducting breast self‐examination and accepting routine breast cancer screening programs, and it can improve patient access to effective treatments . However, the findings are not entirely in accordance with this point.…”
Section: Discussionsupporting
confidence: 88%
“…12 A person's place of residence, that is, metropolis or non-metropolis, affects their access to screening and medical resources, while educational level has an impact on cancer awareness and adherence to treatment. 13 However, the results of studies from different areas or different populations were not in conformity due to the complexity of socioeconomic factors. Moreover, to date, no such study constructed a survival model that includes simplified socioeconomic factors to predict the outcomes of early breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These descriptive statistics of cases and controls show statistically significant differences between the groups for all variables, in line with epidemiologic research (Feller, 2017). Except for mortality, the magnitudes of the differences are relatively modest.…”
Section: 3supporting
confidence: 83%
“…However, women treated with mastectomy are not at risk for ipsilateral breast cancer [47]. Concerning SEP and mammography use, the Swiss findings are mixed [48,49], but we recently reported that women of higher SEP compared to women of lower SEP are more likely to be diagnosed at an early stage [50]. In our present study, breast cancer survivors in general had a similar risk of SPC than the general female population, although an increased risk of SPC was observed in the youngest age-group (< 50 years at time of diagnosis).…”
Section: Discussion In the Context Of The Literaturementioning
confidence: 99%